2013
DOI: 10.1002/jcb.24638
|View full text |Cite
|
Sign up to set email alerts
|

Surface Density of Vascular Endothelial Growth Factor Modulates Endothelial Proliferation and Differentiation

Abstract: Therapeutic strategies aim to regulate vasculature either by encouraging vessel growth for tissue engineering or inhibiting vascularization around a tumor. Vascular endothelial growth factor (VEGF) is essential to these processes, and there are several strategies that manipulate VEGF signaling. Here we develop a method to control the surface density of VEGF, which is covalently attached to tissue culture polystyrene (TCPS), and explore cellular responses to surfaces with varying VEGF densities. We show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…4a ). VEGF and its receptors (including VEGFR1 and VEGFR2) not only have an effect on the vascular differentiation but also play a key role in vascular proliferation 16 18 . qRT-PCR further confirmed that the levels of the VEGFA and its receptors in proximal TGPs were significantly lower in TD chickens at 7 days old, which markedly recovered at 10 and 14 days of age due to the removal of thiram compared with the levels in the normal group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4a ). VEGF and its receptors (including VEGFR1 and VEGFR2) not only have an effect on the vascular differentiation but also play a key role in vascular proliferation 16 18 . qRT-PCR further confirmed that the levels of the VEGFA and its receptors in proximal TGPs were significantly lower in TD chickens at 7 days old, which markedly recovered at 10 and 14 days of age due to the removal of thiram compared with the levels in the normal group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, vasculogenesis refers to the de novo emergence of a vascular network to initiate the formation of blood islands from mesodermal progenitors to hemangioblasts, followed by migration and association of endothelial cells to form a primitive capillary plexus 14 , 15 , whereas angiogenesis refers to the generation of vessels by sprouting or non-sprouting from pre-existing capillaries 12 . In this process, a variety of angiogenic factors, including vascular endothelial growth factor (VEGF) and its receptors 16 18 , the fibroblast growth factor (FGF) family 19 , platelet-derived growth factor (PDGF)-BB and its receptor 20 , 21 , angiopoietin-1 (Ang1), Ang2 and their endothelium-specific receptors such as tyrosine kinase Tie2 (also known as Tek) 22 , 23 , are all widely expressed as primary inducers of vascular development and postnatal angiogenesis 24 , 25 . Among these, blockage of the VEGF receptors VEGFR1 and VEGFR2 contributes to decreased blood vessel formation and bone regeneration 17 .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 M2 macrophages produce arginase-1 (ARG1), mannose receptor (CD206), and IL-10 22 as well as vascular endothelial growth factor (VEGF), 23,24 which supports the homing, migration, and proliferation of endothelial cells. 25 Therefore, further studies are needed to investigate the promotion/inhibition of HUVEC behaviors by the mixture secreted by macrophages on the surface of TiO 2 nanotubes. Accordingly, in this study, we evaluated the inflammatory response to commercially pure Ti (CP) and to TiO 2 nanotubes generated using 20 (TNT20), 40 (TNT40), and 60 V (TNT60).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Such GF-modified biomaterials have been shown to promote in vitro cell proliferation, [7,8] migration [8,9] and differentiation. [10,11] However, most of the studies on the biological modification of materials rely on the addition of a single GF, while in their physiological environment, GFs are often combined, and complex processes such as wound healing or angiogenesis typically involve several signalling proteins possessing synergistic or complementary actions. [12][13][14][15] This generated a growing interest in biomimetic materials delivering or displaying multiple GFs.…”
Section: Introductionmentioning
confidence: 99%